Affordable and quality housing through the low cost housing provision in Malaysia - Idrus, Noraliah; Ho, Chin Siong (2008)
Housing is a major concern for all people in every corner of the world as the wellbeing of a country is reflected in its people enjoying a certain standard of living. Residential and neighbourhood satisfaction is an important indicator of housing quality and condition, which affects individuals quality of life. The factors, which determine their satisfaction, are essential inputs in monitoring the success of housing policies. Housing provision for all in any country is very crucial in order to ensure socialeconomic stability and to promote national development. Therefore the Malaysian government under its 5 year National Plan has introduced the low, medium and high cost housing categories. The housing policy in Malaysia is to provide Malaysians of all income levels, particularly the low-income groups, accessibility to adequate, affordable and quality shelter. It provides direction to housing development in the country which should emphasis human settlement of better quality of life, national integration and unity. This paper will discuss the general scenario of housing in Malaysia particularly the low cost housing.